2017
DOI: 10.3389/fimmu.2017.00826
|View full text |Cite
|
Sign up to set email alerts
|

Novel Modulators of Asthma and Allergy: Exosomes and MicroRNAs

Abstract: Intercellular communication is crucial to the immune system response. In the recent years, the discovery of exosomes has changed the way immune response orchestration was understood. Exosomes are able to operate as independent units that act as mediators in both physiological and pathological conditions. These structures contain proteins, lipidic mediators, and nucleic acids and notoriously include microRNAs (miRNAs). miRNAs are short RNA sequences (around 19–22 nucleotides) with a high phylogenetic conservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 130 publications
0
77
1
2
Order By: Relevance
“…miRNAs differential expression is unlikely to be a mere epigenetic phenomenon of asthma as it has been demonstrated that miRNAs directly or indirectly affect the expression of multiple genes associated with inflammatory response; thus, miR‐16 downregulates TNF α; the miR‐17~92 cluster modifies PTEN ; miR‐155 alters PU.1 , c‐Maf , and SOCS1 ; and miR‐146a regulates TRAF6 and IRAK1 . Others miRNAs have been related to the pathology of asthma and allergy as miR‐21 that is upregulated in steroid‐resistant asthma targeting IL‐12p35 ; the miR‐1248 targeting IL‐5; and miR‐15a inhibiting VEGFA in CD4 + cells . Furthermore, the miRNAs that we have found differentially expressed in eosinophils from asthmatics have predicted targets that may be related to asthma physiopathology: MAPK1 , AKT1 , CDC42 , RHOA , PTEN , SMAD3 , VEGFA , TGFBR1 , and STAT3 using miRSystem (software for miRNA target determination, data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs differential expression is unlikely to be a mere epigenetic phenomenon of asthma as it has been demonstrated that miRNAs directly or indirectly affect the expression of multiple genes associated with inflammatory response; thus, miR‐16 downregulates TNF α; the miR‐17~92 cluster modifies PTEN ; miR‐155 alters PU.1 , c‐Maf , and SOCS1 ; and miR‐146a regulates TRAF6 and IRAK1 . Others miRNAs have been related to the pathology of asthma and allergy as miR‐21 that is upregulated in steroid‐resistant asthma targeting IL‐12p35 ; the miR‐1248 targeting IL‐5; and miR‐15a inhibiting VEGFA in CD4 + cells . Furthermore, the miRNAs that we have found differentially expressed in eosinophils from asthmatics have predicted targets that may be related to asthma physiopathology: MAPK1 , AKT1 , CDC42 , RHOA , PTEN , SMAD3 , VEGFA , TGFBR1 , and STAT3 using miRSystem (software for miRNA target determination, data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to investigate the exosomal load and composition and whether such a process depends on the cellular origins. 41 The exosomal miRNA profile is likely to reflect, in part, the cellular composition of the BALF because exosomes are cellular secretory products. Different cellular compositions of BALF between healthy controls and patients with asthma can result in distinct exosomal miRNAs as different cells produce different exosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, miRNAs have also been shown to function as potential biomarkers and therapeutic target for asthma [12]. e biological roles of exosomal miRNAs have attracted significant interest in the pulmonary field [13,14]. Exosomal miRNAs from the BALF, such as let-7 and miRNA-200, can act as novel biomarkers for asthmatic patients [15].…”
Section: Introductionmentioning
confidence: 99%